Impact of Literacy on the Prevalence, Awareness, Treatment andControl of Hypertension in Iran - Veghari, Gholamreza (Tabriz University of Medical Sciences, 2012)
INTRODUCTION: Hypertension is an important global health concern claiming 7.1 million lives annually. Literacy, as an essential element of the health education, and its relationship with health has previously been studied. However, few studies have been conducted on the association between literacy and health outcomes. To assess the association between educational level and hypertension, awareness and hypertension control in the north of Iran were the main objectives of this study. METHODS: The present study was a population-based cross-sectional study carried out on 3497 subjects aged 15-65 years using stratified and cluster sampling. Interviewers recorded the data using a multidimensional questionnaire, including blood pressure level. Blood pressure was measured three times with 5-minute intervals and defined based on JNC-7. RESULTS: Totally, 21.2 %(741 cases) of our patients suffered from hypertension and illiterate people were significantly more aware of their disease (P=0.011). Among the aware group, at least 89.6% (435 cases) used one method to control their disease; this however was not statistically significant among the educational levels. Control of hypertension was significantly greater in college educated group than in illiterate group (32.4% vs. 68.8%; P=0.001). Logistic regression analysis revealed that illiteracy is a risk factor for hypertension (P<0.001). CONCLUSION: In spite of the fact that awareness in illiterate people was high, the rate of hypertension control was low in this group. Prevention, detection, treatment, and control of hypertension especially in illiterate people should receive high priority.